KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALITAS GURU DI SMPN 3 MUARA SUGIHAN - Jupri, Muhammad (UNISAN JURNAL, 2024)
This research is based on the school principal’s good leadership. In this regard, this research aims to determine the leadership of the school principal in increasing teacher professionalism at SMPN 3 Muara Sugihan. This research uses qualitative research which focuses on natural symptoms and is analyzed using the logic of scientific thinking. The data collection techniques in this research were obtained through observation, interviews, documentation and triangulation. Data analysis was carried out by data reduction, data presentation, and data verification and then formulating conclusions on the results of the research carried out. There are three things stated in this research, namely: (1) the managerial ability of the principal in relation to the chief officer in increasing the professionalism of teachers at SMPN 3 Muara Sugihan has been proven to produce the school’s vision and mission products which have been implemented well, although not all of them, and To achieve this requires good cooperation with all elements of the school; the role of the principal is to create a harmonious atmosphere in the school environment, by giving teachers tasks according to their main duties and functions and teachers can carry out their duties and responsibilities professionally; provide opportunities for teaching staff to improve their profession; (2) the ability of the Principal’s Sense of Business to increase teacher professionalism, as evidenced by the principal’s ability to manage education funds, especially in finding sources of education funds to meet the needs in providing education; (3) the ability of the school principal’s sense of education to increase teacher professionalism, which is proven by the school principal’s ability to carry out mental development, moral development, physical development and artistic development which are carried out in a programmed manner.